Long-Term Outcomes of Proximal Row Carpectomy: A Systematic Review of the Literature - Chim, Harvey; Moran, Steven L. (Journal of Wrist Surgery, 2012)
Purpose Proximal row carpectomy is a well-established technique for the management of wrist arthritis; however, patient selection and long-term durability of proximal row carpectomy is still a matter of controversy. Hence, we conducted a systematic review of the English literature to determine the best evidence on long-term outcomes following proximal row carpectomy.Methods A MEDLINE search using the term “proximal row carpectomy” was performed. A total of 192 studies were identified. All studies with 10 or more years of follow-up were included in the review. Data extracted included patient demographics, indications for surgery, previous surgery, outcome assessment, and information on complications and failures.Results A total of 147 patients from six studies met the inclusion criteria and were included in the study. The majority of patients were male and involved in manual labor. There was no significant difference between the preoperative and long-term postoperative motion. The weighted mean for postoperative grip strength was 68.4% compared with the contralateral side. Disabilities of the arm, shoulder, and hand; patient-rated wrist examination; and Mayo wrist scores were comparable to those reported for four-corner arthrodesis. There were 21 failures (14.3%) requiring re-operation. Failures were not associated with a specific preoperative diagnosis but distributed among patients with Kienböck disease, scaphoid nonunion advanced collapse, and scapholunate advanced collapse arthritis.Conclusions This systematic review confirms the long-term durability of proximal row carpectomy when used for the treatment of wrist arthritis. Although radiocapitate arthritis develops over time in most patients, the clinical significance of this finding is undetermined and does not necessarily correlate with failure of proximal row carpectomy. Poorer long-term outcomes are likely to result in patients engaged in heavy manual labor, whereas better outcomes may be obtained in patients undergoing proximal row carpectomy for trauma or earlier-stage Kienböck disease.
Keywords: proximal row carpectomy; outcomes; wrist; arthritis